2017
DOI: 10.1177/0047287516684979
|View full text |Cite
|
Sign up to set email alerts
|

The “Terminal” Effects of Service Failure on Airlines: Examining Service Recovery with Justice Theory

Abstract: The objective of this research was to examine airline passengers’ service recovery assessments. In addition, the impact of loyalty was examined with relation to postrecovery satisfaction, word-of-mouth communication, and purchase intent. Rawls’s justice theory guided the study. Data were collected via self-reported measure from Mturk and revealed that air travelers’ level of satisfaction of service recovery was impacted by all three justice dimensions. It was further found that the most effective recovery stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 77 publications
5
98
1
Order By: Relevance
“…In testing H4, anger is directly linked to tourists' switching intentions, complaints, and negative WOM in the context of flight delay, which is consistent with previous argument that anger can lead to problem‐focused coping behaviours in service failure context (Bougie et al, ; Migacz et al, ; Soscia, ; Yi & Baumgartner, ) and restaurant settings (Mattila & Ro, ). From a psychological perspective, anger is related to aggression and hostile behaviours (Averill & Kidd, ; Breitsohl & Garrod, ) and has a negative relationship with individual inaction (Mattila & Ro, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In testing H4, anger is directly linked to tourists' switching intentions, complaints, and negative WOM in the context of flight delay, which is consistent with previous argument that anger can lead to problem‐focused coping behaviours in service failure context (Bougie et al, ; Migacz et al, ; Soscia, ; Yi & Baumgartner, ) and restaurant settings (Mattila & Ro, ). From a psychological perspective, anger is related to aggression and hostile behaviours (Averill & Kidd, ; Breitsohl & Garrod, ) and has a negative relationship with individual inaction (Mattila & Ro, ).…”
Section: Discussionsupporting
confidence: 84%
“…Anger is an emotion related to aggressive or hostile behaviour (Averill & Kidd, ; Bonifield & Cole, ). Previous studies have found a positive relationship between anger and consumers' subsequent switching behaviour (Breitsohl & Garrod, ; Kim & Park, ; Mattila & Ro, ), complaining (Bonifield & Cole, ; Bougie et al, ; Gelbrich, ; Soscia, ), and negative WOM (Bonifield & Cole, ; Bougie et al, ; Breitsohl & Garrod, ; Grégoire & Fisher, ; Migacz, Zou, & Petrick, ). However, Sánchez‐García and Currás‐Pérez () compared the effects of anger on behavioural intention in both hotel and restaurant settings and found that anger only predicts switching intentions in a hotel rather than a restaurant setting.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Recently, Migacz et al (2016) found that the most effective recovery strategy for airline management would be to focus on providing compensation beyond customers' expectations.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Mturk has been shown to be more accurate and (often) indistinguishable from many other sources of survey collection [59,60], and more representative of the U.S. population than typical samples of convenience [61]. Furthermore, data gathered from MTurk has been published in leading scholarly journals in marketing, such as Journal of Marketing (e.g., [62,63]) and Journal of Marketing Research (e.g., [64,65]); tourism, such as Tourism Management (e.g., [66,67]) and Journal of Travel Research (e.g., [68,69]). Likewise, top management journals such as Academy of Management Journal (e.g., [70,71] and Journal of Management (e.g., [72]) have also reported MTurk data.…”
Section: Research Participantsmentioning
confidence: 99%